A Field Validated Model of Temporal Variability in Oyster Habitat Suitability - Linhoss, Anna; Mickle, Paul (Frontiers in Marine Science, 2022)
This work presents the development and validation of a spatially and temporally variable oyster habitat suitability model for the western Mississippi Sound, northern Gulf of Mexico. In the work, we 1) develop an oyster habitat suitability model based on existing conditions in one year, 2) forecast habitat suitability throughout the same location in following years, and 3) validate the model using independent data describing field counts of live and recent dead oysters in those following years. The model uses four environmental factors to determine habitat suitability, namely: maximum annual temperature, maximum annual salinity, minimum annual salinity, and minimum annual dissolved oxygen. Overall, the model does not discriminate well between good and poor habitat when the habitat suitability score is less than 0.2; however, when the habitat suitability score is greater than 0.2, there is a high confidence that are more live than recent dead oysters. The results also show that habitat suitability varies by up to 0.45 in any single location (one standard deviation; on a scale from 0 to 1). This is important for evaluating which areas will be most resilient for oyster habitat under a variety of conditions. This study presents the first validated statistical model of temporally and spatially varying oyster habitat suitability.